Functional profile of gastric epithelial cells infected with Helicobacter pylori strains. (June 2016) - Zhang, Ying; Sun, Hui; Chen, Xingxing; Li, Jiaojiao; Zhao, Huilin; Geng, Li; Li, Boqing
Abstract: Helicobacter pylori infection represents a key factor in the etiology of various gastro-duodenal diseases, ranging from chronic gastritis to the development of peptic ulcer disease and end-stage gastric cancer. In the present study, the 26695 and SS1 strains of H. pylori were used to study the differential functional profiles of gastric epithelial cells infected with H . pylori . The apoptosis rates in GES-1 cells were significantly increased 3, 12 and 24 h after H . pylori 26695 and SS1 infection. Moreover, apoptosis by cells infected with the H . pylori 26695 strain was significantly higher than cells infected with the SS1 strain of H . pylori . No significant changes in the proliferation rates of GES-1 cells were observed after H . pylori 26695 or SS1 infection at any time during the experimental period. Exposure to H . pylori 26695 and SS1 induced a significant decline in the adhesion rates of GES-1 cells in a time-dependent manner. Furthermore, H . pylori 26695 infection increased migration of GES-1 cells every hour during the whole experimental period compared with control cells. However, GES-1 cells infected with the H . pylori SS1 strain exhibited migration rates almost stable and comparable to those of control cells. These results indicate that the gastric epithelial cells respond differently depending on the H . pylori strains. This study indicates that the development of different gastric-related diseases may be a H . pylori strain-specific response. Highlights: Helicobacter pylori infection causes imbalance between cell proliferation and cell apoptosis. H . pylori infection promotes the disintegration of proliferative gastric epithelial cells. Each H . pylori strain elicits differential responses in gastric epithelial cells.